Biblical hapax legomena in the Reflection of the Translation (on the Material of the Book of Job from the Vilna Old Testament Book (F 19–262) and the Polish Bibles of the 16th century) - Kozhinowa, Alla; Sourkova, Alena (Slavistica Vilnensis, 2019)
The article examines the linguistic aspects of the translational reflection on hapax legomena from the Book of Job. Lexical correspondences to the Hebrew hapax in Ruthenian (prosta(ja) mova) and Polish are compared with the material from Vilnius Old Testament Florilegium (F 19–262) (approx. 1517–1533), the Radziviłł Bible (Biblia Radzivillovska) (1563), and the Nesvizh Bible (Biblia Nieświeska) (1568–1572) by Symon Budny. All translations demonstrate examples of both etymological interpretation and representation of figurative meaning based on the closest context. Facts of the usage of classical Jewish exegetic comments suggest the existence of a traditional understanding of the “dark places” in the Book of Job.